Систематика та філогенетичні зв’язки видів роду Viburnum L. - Demchenko, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
It was analyzed the results of investigations on taxonomy and volume of Viburnum L. species. Examined of the phyllogenetic relations of the genus Viburnum.